Effects of Light on the Ochratoxigenic Fungi Aspergillus ochraceus and A. carbonarius - Haiyong Zhang; Gang Wang; Qingli Yang; Xu Yang; Yongquan Zheng; Yang Liu; Fuguo Xing (Toxins, 2021)
Ochratoxin A (OTA) usually contaminates agricultural products such as grapes, oatmeal, coffee and spices. Light was reported as an effective strategy to control spoilage fungi and mycotoxins. This research investigated the effects of light with different wavelengths on the growth and the production of OTA in Aspergillus ochraceus and Aspergillus carbonarius. The results showed that the growth of both fungi were extremely inhibited by UV-B. Short-wavelength (blue, violet) significantly inhibited the production of OTA in both fungi, while the inhibitory effect of white was only demonstrated on A. ochraceus. These results were supported by the expression profiles of OTA biosynthetic genes of A. ochraceus and A. carbonarius. To clarify, the decrease in OTA production is induced by inhibition or degradation; therefore, the degradation of OTA under different wavelengths of light was tested. Under UV-B, the degradation rate of 10 μg/mL OTA standard pure-solution samples could reach 96.50% in 15 days, and the degradation effect of blue light was relatively weak. Furthermore, infection experiments of pears showed that the pathogenicity of both fungi was significantly decreased under UV-B radiation. Thus, these results suggested that light could be used as a potential target for strategies in the prevention and control of ochratoxigenic fungi.